Climate-Resilient Robotic Facades: Architectural Strategies to Improve Thermal Comfort in Outdoor Urban Environments using Robotic Assembly - Fleckenstein, Julia; Molter, Philipp Lionel; Chokhachian, Ata; Dörfler, Kathrin (Frontiers in Built Environment, 2022)
In the context of dense urban environments and climate change, pedestrians' thermal experience plays an increasingly significant role in people’s health and well-being. In this research, the authors combine the fields of architecture, climate-responsive design, and robotic fabrication with the goal of investigating strategies to improve outdoor thermal comfort for pedestrians in cities with frequent extreme heat events. Based on a case study in the city of Munich, this paper presents findings into the technological approaches and methods for location-specific climate-resilient brick facades using robotic assembly. To achieve this goal, different bricklaying patterns were investigated to create a self-shading effect and thus reduce solar radiation and ultimately achieve an improved thermal condition for pedestrians moving along urban facades at street level. Using computer-aided microclimate simulation, generic self-shading brick pattern designs were tailored to highly location-specific microclimate requirements. Robotic assembly technology was used to produce such tailored, non-standard brickwork facades. The results of this research led to a data-informed design process with a demonstrator object being realized at 1:1 scale with a height of 2m and a length of 3m using a collaborative robot on site. Thermal measurements on the built demonstrator provided indications of reduced surface temperatures despite high solar radiation and thus validated the location-specific self-shading effects according to solar radiation simulation.